2014
DOI: 10.15270/50-2-397
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Evidence of Violence in Partner Relationships With Regard to Xhosa African Women

Abstract: This article reports on how African women understand the forms and meaning of violence in partner relationships. The findings suggest that many African women experience physical, emotional and economic abuse. Some of the reasons for abuse which emerged include a patriarchal system, alcohol abuse, infidelity and failure to support children financially. The influence of Xhosa African practices on violent partner relationships was explored. The study indicates a need for ethnically sensitive interdisciplinary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…South Africa has a notoriously low reporting rate of violence and violent acts [31] and respondents, although having provided consent and been in a private environment, may not have felt comfortable to report such acts to the fieldworker. Furthermore, studies have found that in the South African context women often accept such violence due to a patriarchal system, alcohol abuse, infidelity and failure to support children financially [32].…”
Section: Discussionmentioning
confidence: 99%
“…South Africa has a notoriously low reporting rate of violence and violent acts [31] and respondents, although having provided consent and been in a private environment, may not have felt comfortable to report such acts to the fieldworker. Furthermore, studies have found that in the South African context women often accept such violence due to a patriarchal system, alcohol abuse, infidelity and failure to support children financially [32].…”
Section: Discussionmentioning
confidence: 99%
“…A number of social norms have been identified that singly or jointly increase the risk of women experiencing IPV. These include cultural and religious practices such as female genital mutilation (Kandala & Komba, 2015); male dominance and superiority over women within families and society (McCloskey et al, 2016); acceptance of wife-beating as a way of 'correcting a stray wife' and a sign of love (Oyediran & Feyisetan, 2017); family privacy and stigma associated with divorce or being unmarried (Matavire, 2012); women's responsibility to maintain a marriage and their reproductive role (Shamu, Abrahams, Zarowsky, Shefer & Temmerman, 2013); social norms surrounding lobola (bride-price) payment, which acts as a compromising factor in IPV tolerance (Mesatywa, 2014); and men's entitlement to sex (Mukanangana, Moyo, Zvoushe & Rusinga, 2014). These social norms have been ingrained in some women in rural areas to such an extent that there is a tolerance of abuse and thus a heightened vulnerability to IPV.…”
Section: Social Norms and Ipvmentioning
confidence: 99%
“…Furthermore, attributes of masculinity are associated with dominance and aggression, with men holding the decision-making power in marriages (Mesatywa, 2014;Clark et al, 2018). Traditionally lobola (bride-price), referred to as roora in Zimbabwe, has always been regarded as a noble practice that gives status to both men and women.…”
Section: Social Norms and Ipvmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanda and Warms (2014) suggest that the concept of a 'real man' is a widespread cultural pattern where a man proves to himself that he is now able to 'control' women, is successful in competition with other men, and is aggressive. In line with Nanda and Warms (2014) beliefs of what is a real man, the patriarchal belief system that predominates within the Xhosa culture contributes to the widespread gender-based violence in South Africa (Mesatywa, 2014). Male initiation processes often include rituals where boys are expected to bear physical pain without showing emotions and these rituals are known as part of the rite of passage (Nanda & Warms, 2014).…”
mentioning
confidence: 96%